Knowledge About Dementia Among Family Caregivers With a Turkish or Moroccan Immigrant Background: Development and Validation of a Dementia Knowledge Scale - Nienke van Wezel; Iris van der Heide; Walter L.J.M. Devillé; Marco M. Blom; Rianne Hoopman; Anneke L. Francke (SAGE Publishing, 2022)
Objective: To describe the development and validation of the Dementia Knowledge Scale (DKS) among family caregivers with a Turkish or Moroccan immigrant background. Methods: The 11 items of the DKS, selected by professionals and people with a Turkish or Moroccan background, were translated and adapted in Turkish and Dutch. The feasibility, comprehensibility and appropriateness of the 2 language versions were examined. Subsequently, both languages were assessed among caregivers from these groups. The internal consistency of both language versions was determined by calculating Cronbach's α. The known group validity was determined by comparing mean scores between subgroups. Results: Both language versions of the DKS were considered feasible, comprehensible, and appropriate. A total of 117 caregivers with a Turkish background completed the Turkish version of the DKS and 110 with a Moroccan background the Dutch version. The Turkish version showed adequate internal consistency but the Dutch version did not. No differences were found in mean scores between those with a low level of education versus those with a higher level; those who frequently provided care versus those who did so less frequently; and those who lived together with a person with dementia versus those who did not. Conclusions: The DKS is feasible, comprehensible and reliable and can be used among groups with an immigrant background. Practice Implications: The DKS provides insight into various aspects of dementia knowledge, including knowledge about risk factors and symptoms, among caregivers with a Turkish or Moroccan background, and thereby supports the development of tailored education for these groups.